Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer:
(y^2+1)(x^2+1)=k
Step-by-step explanation:
It looks like it is possibly separatable.
Let's try.
Factor the x out on first term and factor the y out on second term:
x(y^2+1)dx+y(x^2+1)dy=0
Subtracting y(x^2+1)dy on both sides:
x(y^2+1)dx=-y(x^2+1)dy
Divide both sides by (y^2+1)(x^2+1):
x/(x^+2+1)dx=-y/(y^2+1)dy
Integrate both sides..
Use substitution u=x^2+1 and v=y^2+1...so du= 2x dx and dv=2y dy.
.5du/u=-.5dv/v
.5ln|u|=-.5ln|v|+c
Multiply both sides by 2:
ln|u|=-ln|v|+c
Plug in our substitutions :
ln|x^2+1|=-ln|y^2+1|+c
Absolute values unnecessary since insides are positive always.... also -ln(y^2+1)=ln(1/(y^2+1))
e^ on both sides:
x^2+1=k(1/y^2+1)
(y^2+1)(x^2+1)=k
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.